1983
DOI: 10.1007/bf01574261
|View full text |Cite
|
Sign up to set email alerts
|

Human parathyroid hormone gene (PTH) is on short arm of chromosome 11

Abstract: The human gene for parathyroid hormone (PTH) was chromosomally mapped using human-rodent hybrids and Southern filter hybridization of cell hybrid DNA. A recombinant DNA probe containing human PTH cDNA insert (pPTHm122) hybridized to a 3.7-kb fragment in human DNA cleaved with the restriction enzyme EcoRI. By correlating the presence of this fragment in somatic cell hybrid DNA with the human chromosomal content of the hybrid cells, the PTH gene was mapped to the short arm of the chromosome 11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…Venous blood was obtained, after informed consent, from 60 family members; 5 were affected males, 11 were carrier females, and 44 were unaffected (26 males, 18 females). Of the 60 members, 50 (4 affected, 7 carriers, and 39 unaffected) were from four generations of kindred W/81 and 10 (1 affected, 4 carriers, and 5 unaffected) were from three generations of kindred P/60.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Venous blood was obtained, after informed consent, from 60 family members; 5 were affected males, 11 were carrier females, and 44 were unaffected (26 males, 18 females). Of the 60 members, 50 (4 affected, 7 carriers, and 39 unaffected) were from four generations of kindred W/81 and 10 (1 affected, 4 carriers, and 5 unaffected) were from three generations of kindred P/60.…”
Section: Methodsmentioning
confidence: 99%
“…1). 7 ofthese probes (782, D2, 99.6, C7, 754, pOTC, and L1.28) were from the short arm and 10 others (pDp34, 30RIb, pX45h, 52A, FIX [Factor IX], CX55.7, 4D.8, Mnl2, Stl4, and DX 13) were from the long arm ofthe X chromosome. These polymorphic probes define the loci DXS85, DXS43, DXS41, DXS28, DXS84, OTC, DXS7, DXYS1, DXS37, DXS100, DXS51, F9, DXS105, DXS98, DXS33, DXS52, and DXS15, respectively (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PTH gene is located on the short arm of chromosome 11 [2]. PTH is synthesized as a large polypeptide (pre-pro PTH) containing 115 amino acids that undergoes two successive proteolytic cleavages to yield the 84 amino-acids PTH, the main form of the hormone stored in and secreted from the parathyroid glands.…”
Section: Pth Secretion and Actionmentioning
confidence: 99%
“…Several genes such as the human 83-globin gene cluster (HBBC), the parathyroid hormone (PTH) gene, the oncogene HRASI (formerly termed c-Ha-ras-1), and the insulin gene have been assigned to the short arm of chromosome 11 (1)(2)(3)(4)(5). By using DNA polymorphisms for linkage analysis, it has been shown that PTH, HBBC, HRASI, and the insulin gene are closely linked to each other (6,7).…”
mentioning
confidence: 99%